2023
DOI: 10.1002/hbm.26492
|View full text |Cite
|
Sign up to set email alerts
|

Are we really targeting and stimulating DLPFC by placing transcranial electrical stimulation (tES) electrodes over F3/F4?

Ghazaleh Soleimani,
Rayus Kuplicki,
Jazmin Camchong
et al.

Abstract: In many clinical trials involving transcranial electrical stimulation (tES), target electrodes are typically placed over DLPFC with the assumption that this will primarily stimulate the underlying brain region. However, our study aimed to evaluate the electric fields (EF) that are actually delivered and identify prefrontal regions that may be inadvertently targeted in DLPFC tES. Head models were generated from the Human Connectome Project database's T1 + T2‐weighted MRIs of 80 healthy adults. Two common DLPFC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…An RCT by Boggio et al 13 found that excitatory rTMS over the right DLPFC exerted a greater treatment effect than did excitatory rTMS over the left DLPFC 13 . The theoretical effectiveness of stimulation over the aforementioned frontopolar area had been addressed in several reports 14–17 . To address the mixed findings in the literature, researchers have conducted traditional pairwise meta‐analyses 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…An RCT by Boggio et al 13 found that excitatory rTMS over the right DLPFC exerted a greater treatment effect than did excitatory rTMS over the left DLPFC 13 . The theoretical effectiveness of stimulation over the aforementioned frontopolar area had been addressed in several reports 14–17 . To address the mixed findings in the literature, researchers have conducted traditional pairwise meta‐analyses 18,19 .…”
Section: Introductionmentioning
confidence: 99%